Pengaruh Keseimbangan Kehidupan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan: Studi Kasus pada Perum Bulog Kantor Wilayah Bengkulu - Roman Destian Pahrori; Fauzan; Markoni (Economic Reviews Journal, 2024)
The purpose of this study was to determine the effect of work-life balance and work discipline partially and simultaneously on the performance of employees of Perum BULOG Bengkulu Regional Office. The population used is employees of the Bengkulu Regional Perum BULOG company with a total population of 32 employees. The nature of the research used is (explanatory research). Sampling in this study was carried out with a saturated sample technique which means that every employee of Perum BULOG Bengkulu Regional Office became a research sample and with sampling using questionnaires that were ready to be distributed, documentation techniques, and library techniques as a basis for sampling. Data research methods in this study are research instruments in the form of validity tests and reliability tests, data analysis techniques including classical assumption tests in the form of multicollinearity tests, heteroscedasticity tests, and normality tests. Continued to test multiple linear regression and hypothesis testing. The results of the research obtained that the first hypothesis of work life balance has no partial effect on employee performance at the Perum Bulog Regional Office of Bengkulu, the second hypothesis of work discipline has a partial positive effect on employee performance at the Perum Bulog Regional Office of Bengkulu and the third hypothesis of work life balance and work discipline have a simultaneous effect on employee performance at the Perum Bulog Regional Office of Bengkulu.